Issues of the Research of The Little Traveller’s Book. Polemic Discourse - Lemeškin, Ilja (Knygotyra, 2023)
A polemical article reacts to the plenary part of the conference Francysk Skaryna and the Renaissance book culture. Skaryna’s Little Travel Book turns 500, held in Vilnius on 22–23 September 2022. After a review of the history of Little Traveler’s Book studies since 1971, five problems in the study of the first printed book of the GDL, touched on in S. Temchin’s plenary speech The Place of Printing of Francysk Skaryna’s “Little Traveller’s Book”: New Assumptions are discussed. In addition, two other aspects related to the study of place and time of printing: genre predetermination and application of modern methods to the study of Little Traveler’s Book are investigated.